THE EFFECT OF DEPOSITS AND LOANS ON NET PROFIT AT NATIONAL COMMERCIAL BANKS LISTED ON THE IDX - Didin Rasyiddin Wahyu; Aslihah Aslihah (SEAN Institute, 2023)
This study aims to determine the effect of third party funds and credit distribution on operating income at Commercial Banks listed on the Indonesia Stock Exchange for the 2018-2022 period. The method used in this study is the Quantitative Approach. The population of this study is 42 National Commercial Banks listed on the Indonesia Stock Exchange and the determination of the number of samples using the purposive sampling method is 7 banks with financial statement data for the 2018-2022 period. Results of Hypothesis Test Testing, Third Party Funds Against Net Profit obtained a calculated value of > ttable (2.308 > -2.034) and a significant value of 0.028 < 0.05, then Ha was accepted and Ho was rejected. Therefore, it can be seen that there is a significant influence of Third Party Funds (DPK) on Net Profit in National General banking. Credit to Net Profit is obtained Because the calculated value of > table (7.135 > 2.034) and the significant value of 0.000 < 0.05, Ho is rejected and Ha is accepted. Based on significant tests, it was found that there was a significant influence between Credit and Net Profit in national general banks. Based on Test F, it is known that the value of Fcalculate > Ftable (76.649 > 3.35) and the significance value of 0.000 < 0.05, then Ho is rejected and Ha is accepted. Based on the significance test, there is an effect of Third Party Funds (DPK) and Credit together on Net Profit in national general banks. In conclusion, there is a partial influence between third party funds on Net Income, and there is an influence between credit on Net Income. Meanwhile, simultaneously there is a joint influence between third party funds and credit on Net Profit